Interaccion phitophthora infestans-bacterias en el filoplano de la papa y su relacion con las condiciones climaticas en Cuba - Stefanova, M.=700 1 Perez, I.; Coronado, F.; Larrinaga, L.
(Es, En)
Ilus., 12 ref.
Keywords: SOLANUM TUBEROSUM; PHYTOPHTHORA INFESTANS; PSEUDOMONAS; ERWINIA; CUBA